PEMBENTUKAN VITAMIN B-12 PADA FERMENTASI KEDELAI DENGAN ISOLAT Rizophus oryzae dan Klebsiella Peneumonae - Salahudin, Farid (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2016)
Kobalamin (vitamin B-12) is an important nutrition that good for brain and neuron. Usually, kobalamin can found in animal or fish but in tempeh we can found it. In tempeh processing Rhizophus oligosporus was contaminated of Klebsiella pneumonae and Citobacter freudii and Kobalamin was produced. In other research K. peneumonae and C. freundii has inoculated in soy bean and could increased the concebtration of kobalamin ( Keuth S. and B Bisping, 1994. The aim in this research is to know the effect of combinated of K peneumonae and R. oryzae for concentration of kobalamin in soy bean fermentation. This research was conducted by inoculated the combination isolate and incubated for 1-2 days. The best formula was produced to soya milk.The best formula is 2 days fermentation with combinated isolate R. oryzae and K. peneumonae